2020
DOI: 10.1187/cbe.19-07-0134
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Equitable Outcomes in Introductory Biology Courses through Use of a Dual Domain Pedagogy

Abstract: Recent studies demonstrate that significant learning gains can be achieved when instructors take intentional steps to address the affective components of learning. While such efforts enhance the outcomes of all students, they are particularly beneficial for students from underrepresented groups and can reduce performance gaps. In the present study, we examined whether intentional efforts to address the affective domain of learning (through growth mindset messaging) can synergize with best practices for address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…For example, sharing anecdotes about their own struggles in learning biology ( Goldman and Goodboy, 2014 ), having class policies that indicate ways students can make up missed work ( Young-Jones et al ., 2019 ), or using nonverbal behaviors like eye contact and smiling ( Allen et al ., 2006 ). These, along with other practices derived from the literature related to autonomy-supportive practices, may be ways to increase the persistence of students in the biology major, especially students historically underserved in science ( Bauer et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, sharing anecdotes about their own struggles in learning biology ( Goldman and Goodboy, 2014 ), having class policies that indicate ways students can make up missed work ( Young-Jones et al ., 2019 ), or using nonverbal behaviors like eye contact and smiling ( Allen et al ., 2006 ). These, along with other practices derived from the literature related to autonomy-supportive practices, may be ways to increase the persistence of students in the biology major, especially students historically underserved in science ( Bauer et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although many articles do not define the exact parameters of active learning, the research has demonstrated the positive effects of active learning on student achievement and affect across multiple contexts. For example, researchers demonstrated that active learning yields disproportionate learning gains among the most at-risk student groups, such as first-generation college attendees and those who identify with races/ethnicities historically underrepresented in STEM fields (Beichner et al, 2007;Haak et al, 2011;Eddy and Hogan, 2014;Ballen et al, 2017;Wilton et al, 2019;Bauer et al, 2020). Additionally, a meta-analysis conducted by Theobald et al (2020) demonstrated that active learning narrows achievement gaps for underrepresented students in undergraduate STEM disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…Two independent groups reported using metacognitive interventions with students enrolled in a general chemistry I and introductory biology course, respectively, demonstrated a selective effect on underrepresented minority students by reducing the achievement gap. [18][19][20] The present study investigates undergraduate Biochemistry students' self-reported mindset beliefs and their implications for students' academic performance. Our research questions were (1) would growth mindset interventions promote a growth mindset in biochemistry students?…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of metacognitive interventions (although assumed to be effective across disciplines) has not been fully investigated in biochemistry classrooms. Two independent groups reported using metacognitive interventions with students enrolled in a general chemistry I and introductory biology course, respectively, demonstrated a selective effect on underrepresented minority students by reducing the achievement gap 18–20 …”
Section: Introductionmentioning
confidence: 99%